Pengaruh Gaya Belajar, Disiplin, Minat dan Lingkungan Terhadap Hasil Belajar - Elfina Samoiri (Universitas Pendidikan Ganesha, 2026)
This study aims to examine the influence of learning style, learning discipline, learning interest, parental education level, and school environment on the learning outcomes of Grade X Phase E students in Economics at SMA Negeri 1 Sipora. The research used a quantitative method with a sample of 89 students, and data were collected using questionnaires. The results showed that all five variables had a positive and significant effect on learning outcomes. Partially, each variable had a t-value greater than the t-table. Simultaneously, the F-value was 14.743 > 2.48 with a significance value of 0.000 < 0.05, indicating that all variables together significantly affected students’ learning outcomes.